Aplicação de métodos cognitivos em ambientes virtuais de aprendizagem para os surdos na busca da construção de aprendizagem - Sousa, Gilcifran Vieira de (2020)
This study aims to develop a research and analysis of virtual environments aimed at learning for the education of the deaf, aiming to contribute to the applicability of new technologies and teaching methodologies in the digital inclusion of educators with special educational needs auditory. To identify the cognitive models linked to new formalizations and educational transmission systems for the deaf, by researching and analyzing the hypermedia environments for learning with content formalization to be used by Deaf students, analyzing the resources of the new Information and Communication Technologies), research and analysis of the learning of the deaf through the virtual environments aimed at them, highlighting the research on digital content formalization, the investigation of the problems arising from cognitive dynamics in digital environments and the new methodologies for special education, considering these are all the feedbacks that must be had to work with digital inclusion for people with special educational hearing needs. The theoretical basis of this research is articulated with the concepts of cognitive models, educator training, Internet use, applicability of new information technologies, hypermedia environments, use of new teaching methodologies with the use of information repository for special auditory education. Based on these theoretical assumptions, it was possible to conduct the training process to favor the contextualization of teachers' pedagogical practice and the use of new information technologies and to mediate the analysis of strategies to solve the problems detected in the teaching environment for the deaf. It is concluded that the planning of an Inclusive Digital Information Architecture, focused on accessibility, usability, information and communication technologies can enable the digital and social inclusion of Deaf users in Internet computing environments